The Conserved Cys-2232 in Clostridioides difficile Toxin B Modulates Receptor Binding - Chung, Soo-Young; Schöttelndreier, Dennis; Tatge, Helma; Fühner, Viola; Hust, Michael; Beer, Lara-Antonia; Gerhard, Ralf (Frontiers in Microbiology, 2018)
Clostridioides difficile toxins TcdA and TcdB are large clostridial glucosyltransferases which are the main pathogenicity factors in C. difficile-associated diseases. Four highly conserved cysteines are present in all large clostridial glucosyltransferases. In this study we focused on the conserved cysteine 2232 within the combined repetitive oligopeptide domain of TcdB from reference strain VPI10463 (clade I). Cysteine 2232 is not present in TcdB from hypervirulent strain R20291 (clade II), where a tyrosine is found instead. Replacement of cysteine 2232 by tyrosine in TcdBV PI10463 reduced binding to the soluble fragments of the two known TcdB receptors, frizzled-2 (FZD2) and poliovirus receptor-like protein-3/nectin-3 (PVRL3). In line with this, TcdBR20291 showed weak binding to PVRL3 in pull-down assays which was increased when tyrosine 2232 was exchanged for cysteine. Surprisingly, we did not observe binding of TcdBR20291 to FZD2, indicating that this receptor is less important for this toxinotype. Competition assay with the receptor binding fragments (aa 1101–1836) of TcdBV PI10463 and TcdBR20291, as well as antibodies newly developed by antibody phage display, revealed different characteristics of the yet poorly described delivery domain of TcdB harboring the second receptor binding region. In summary, we found that conserved Cys-2232 in TcdB indirectly contributes to toxin–receptor interaction.